Pragmatics of Prophetic Pedagogy: A Discourse Analysis of Directive Speech Acts in Hadith Literature - Dien Nur Chotimah; Sutaman Sutaman; Mamluatul Hasanah (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
This study aims to analyze the forms of directive speech acts in al-Rasūl al-Mu’allim and explain it’s the pedagogical functions. This research uses a descriptive qualitative approach with a pragmatic perspective and speech act theory. The research data is in the form of utterances that contain directive illocution in the hadīths collected in al-Rasūl al-Mu’allim. Data were analyzed through identification, classification, and interpretation of the illocution function based on the context of hadīth. The results of the study show that the directive speech act is realized through three main forms, namely instruction as a pedagogical directive, advice as a persuasive directive, and guiding and instructional directive. These findings show that the Prophet's pedagogical communication is not only oriented to the direction of actions and behaviour, but also to the formation of understanding and internalization of values. This research contributes to enriches the understanding of prophetic pedagogy from a linguistic-pragmatic perspective.